KNOWLEDGE OF DENTAL AND MOUTH HEALTH WITH THE BEHAVIOR OF ARECA NUT CHEWING OF ADOLESCENTS IN YAPEN ISLANDS REGENCY - Arisjulyanto, Dedy; Tipawael, Yohanis R.; Parawangsa, M.; Purba, Ellen R. V. (Pusat Riset dan Inovasi Nasional, 2022)
Background: Dental and oral health problems in the community, one of which arises because of behavioral factors or attitudes of ignoring dental and oral hygiene. In Indonesia, dental and oral health problems are relatively high, based on data from the 2018 Basic Health Research that 57.6% of the Indonesian population has dental and oral health problems with 10.2% of dental health workers. Papua Province has dental and oral health problems as of 48. The lowest tooth brushing behavior in Indonesia is 54.4% from the national data of 94.7% with a ratio of dental medical personnel still very low at 8%. Methods: The design of this study used a cross-sectional study, the sample used the Probability Proportional Size sampling technique and obtained 90 respondents, and the data analysis in this study used the chi-square test. Results: Based on the results of research and discussion in this study, the distribution of respondents with knowledge of Dental and oral health with the poor category as much as 58.9%, the sufficient category 20%, and the good category as much as 21.1%, the distribution of respondents who have chewing betel nut behavior is 66.7%, and do not have betel nut chewing behavior 33.3%, and the results of the analysis using the chi-square test obtained p-value 0.000 < = 0.05. Conclusion: there is a relationship between the level of knowledge of respondents about dental and oral health with betel nut chewing behavior in the Yapen Islands Regency. It is necessary to do health promotion about dental and oral health in the Yapen Islands Regency. It can increase the knowledge and behavior of adolescent health in maintaining dental and oral health in the Yapen Islands Regency.